Return to Ixil : Maya Society in an Eighteenth-Century Yucatec Town - Christensen, Mark Z.; Restall, Matthew, 1964- (Book collections on Project MUSE., 2019)
"An examination of 100+ previously unstudied colonial-era Maya wills from the Yucatec town of Ixil. These testaments--some of the only surviving documentation of colonial inhabitation--offer unprecedented depictions of material and spiritual life from 1738 to 1779 and are rare and rich resources of Maya language"--Provided by publisher